Marketing Behaviour of Organic Farmers in Karur district of Tamil Nadu - Raahinipriya, P; Jansi Rani, R (Journal of Extension Education, 2019)
In the recent past, most of the developed countries and some of the developing countries are returning to organic farming cultivation. For sustaining a healthy ecosystem there is a need for adoption of organic farming in India. The study was conducted in Karur district of Tamil Nadu to assess the marketing behavior of organic farmers. Nearly three-fourths of the respondents had medium level of marketing behavior.